Perceptions of Tenth Grade Students at Public Schools in Jerash Governorate of Vocational Education - Safaa Bani Hamdan (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to identify the perceptions of vocational education among tenth grade female students from public schools in Jerash Governorate in Jordan. The study also sought to determine if there were significant differences in participants' responses due to student achievement level, level of parent education, and family income. The study used a descriptive survey method. The study sample consisted of (300) female students who were randomly selected from public schools in the city of Jerash in Jordan. To achieve the study objectives, a questionnaire was developed to measure the perceptions of 10th grade students about vocational training. The questionnaire included 25 Likert-like items with satisfactory psychometric properties. Statistical methods used to answer the study questions were: means and standard deviations, frequencies and percentages, one-way analysis of variance, Scheffe test, and Cronbach alpha coefficient. The study found that the level of perceptions of tenth grade female students of vocational education came to a high degree. The study showed that there were statistically significant differences due to the effect of students' achievement level favoring higher levels. The results also indicated significant differences due to the effect of the level of education of the parents in favor of BA degree or above, and due to the effect of average household income. The researcher recommends raising the level of awareness of society and its institutions of the importance of vocational education in general, especially the education directed to females.